2017
DOI: 10.1186/s13024-017-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cortical FADD protein is associated with clinical dementia and cognitive decline in an elderly community sample

Abstract: BackgroundFADD (Fas-associated death domain) adaptor is a crucial protein involved in the induction of cell death but also mediates non-apoptotic actions via a phosphorylated form (p-Ser194-FADD). This study investigated the possible association of FADD forms with age-related neuropathologies, cognitive function, and the odds of dementia in an elderly community sample.MethodsFADD forms were quantified by western blot analysis in dorsolateral prefrontal cortex (DLPFC) samples from a large cohort of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Additionally, this latter study also showed, in line with the present results, that while FADD was regulated in the hippocampus following repeated drug administration, p-FADD was not . Besides, a similar absence on p-FADD regulation was observed in an aged population in which a lower contents of FADD was associated with poorer cognitive performance (Ramos-Miguel et al, 2017), suggesting a more important role for total FADD form in cognition and ageing. Since FADD is decreased with ageing (Hernández-Hernández and García-Fuster, 2017) and in age-related neuropathologies (i.e.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Additionally, this latter study also showed, in line with the present results, that while FADD was regulated in the hippocampus following repeated drug administration, p-FADD was not . Besides, a similar absence on p-FADD regulation was observed in an aged population in which a lower contents of FADD was associated with poorer cognitive performance (Ramos-Miguel et al, 2017), suggesting a more important role for total FADD form in cognition and ageing. Since FADD is decreased with ageing (Hernández-Hernández and García-Fuster, 2017) and in age-related neuropathologies (i.e.…”
Section: Discussionsupporting
confidence: 55%
“…Hernández-Hernández and García-Fuster, 2017) and in age-related neuropathologies (i.e. FADD as a putative biomarker of the cognitive decline associated with the course of clinical dementia; see Ramos-Miguel et al, 2017). In particular, this latter study demonstrated that cortical FADD protein was decreased in an elderly, community-based cohort of subjects with dementia, and that loss of FADD was associated among other things with poorer cognitive function and increased risk of dementia (Ramos-Miguel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disrupted FADD phosphorylation has been inversely correlated with tumor aggressiveness in T-cell lymphoblastic lymphomas [98]. Moreover, decreased FADD is associated with cognitive impairment and clinical dementia in the elderly [99]. In addition, a recent review has explored the roles of FADD in the context of cancer and inflammation, highlighting the impact of translational and post-translational modifications in its multiple functions [34].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…In the literature, an association of FADD increase with poor clinical outcome has been described in many solid tumors [4,5,6,7,8,9,10,18,109,150,151,152]. In contrast, a reduction of FADD has been reported in fewer tumor types, among them hematological malignancies [11,12,13,14,15], but also in pathologies different from cancer like dementia [153]. Altered levels of phosphorylated FADD have also been reported, either a reduction [12,13,154,155,156] or an increase [5,7,37,98,100,101,102], but in all cases associated with poor outcome.…”
Section: Clinical Implications Of Fadd Alterations In Cancermentioning
confidence: 99%